The Systematic Literature Review: Schools That Successfully Implement Technology-Based Learning Models - Affria, Anggi; Mansis, Ilhan; Maulana , Mario; Aditya , Rahmad; Andikos , Adi Fitra (The Future of Education Journal, 2024)
This article discusses the implementation of technology-based learning models that have been successful in several schools, with an emphasis on improving the quality of education and student learning experiences. The author identifies several schools in Indonesia that have successfully integrated technology into their learning systems, such as the use of learning platforms, interactive applications, and other digital media. The article also provides real-life examples from schools that have adopted technology-based learning models, such as Yayasan Ponpes Al-Ma'arif and Ponpes Nurul Izzah. By incorporating technology into the learning process, these schools have been able to create more effective and innovative learning environments. Additionally, the article discusses the challenges and opportunities faced by schools in the process of digital transformation